INTEGRATING VALUES-ORIENTED DEEP LEARNING TO PROMOTE GLOBAL CITIZENSHIP ATTITUDES AMONG PRIMARY LEARNERS: MENGINTEGRASIKAN PEMBELAJARAN DALAM (DEEP LEARNING) BERORIENTASI NILAI UNTUK MENINGKATKAN SIKAP KEBANGSAAN GLOBAL DI KALANGAN SISWA SEKOLAH DASAR - Risma Inayatur Amaliyah; Muhlasin Amrullah; Mahardika Darmawan Kusuma Wardana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the effect of applying deep learning integrated with the values of QS. Al-Hujurat verses 9–13 on strengthening elementary school students' attitudes toward global diversity. The study uses a quantitative approach with a one-group pretest–posttest pre-experimental design. The research subjects consisted of 34 fifth-grade students at SDN Wonoplintahan 2. The research instrument was a global diversity attitude test that included indicators of empathy, tolerance, appreciation of differences, solidarity and cooperation, and global responsibility. The Shapiro–Wilk normality test, paired sample t-test, and Eta effect size were used to analyze the data. All analyses were conducted using SPSS 25. The results showed a significant increase in global diversity attitude scores after the intervention, with a large effect size and a significance value of 0.000 (<0.05). These results indicate that QS. Al-Hujurat can effectively and sustainably shape the global diversity attitudes of elementary school students.